Hubungan Dukungan Sosial dengan Kepercayaan Diri Pengguna Narkoba di Klinik Pratama BNNP Sumatera Barat - Violensia, Nadea; Ardi, Zadrian (Lembaga Yasin AlSys, 2024)
This research is motivated by the phenomenon of drug users who are undergoing the rehabilitation process. Those who use drugs will be considered criminals, with these very negative impacts resulting in changes in their social environment, this is what causes a low sense of self-confidence in drug users. This research aims to describe: (1) social support, (2) self-confidence of drug users and, (3) examine the relationship between social support and self-confidence of drug users. This type of research uses a quantitative approach with a research method, namely a correlational descriptive method. The population of this study was 31 rehabilitation patients at the West Sumatra BNNP pratama clinic with a sample size of 31 patients using a total sampling technique. Based on research findings, namely, (1) overall social support is in the high category, (2) overall self-confidence of drug users is in the high category, (3) there is a significant positive relationship in the medium category (0.579) between social support and user self-confidence drugs at the West Sumatra BNNP pratama clinic. The implications for counseling services are in the form of individual counseling services, then group guidance services and family counseling.